INFLUENCE INVESTMENT DECISIONS AND DIVIDEND POLICY ON COMPANY VALUE MEDIATED BY FINANCIAL PERFORMANCE - Ni Nyoman Nuryanti Bella; I Made Dauh Wijana; I Wayan Widnyana; I Nengah Suardhika (Penelitian dan Pengembangan Ilmu, 2026)
This study aims to analyze the influence of investment decisions and dividend policies on firm value, with financial performance as a mediating variable, in property companies listed on the Indonesia Stock Exchange for the 2021–2024 period. This study uses secondary data in the form of annual financial reports. The study population consisted of 62 companies, using a purposive sampling technique, resulting in 248 observational samples. Path analysis and the Sobel test were used to examine the mediating role of the data. The research results show that investment decisions and dividend policy have a positive and significant effect on firm value. Investment decisions and dividend policy also have a positive and significant effect on financial performance. Furthermore, financial performance has a positive and significant effect on firm value. The mediation test results indicate that financial performance mediates the influence of investment decisions and dividend policy on firm value. The findings of this study indicate that improving the quality of investment decisions and dividend policies, supported by strong financial performance, can increase company value. This research is expected to contribute to company management, investors, and future researchers in understanding the factors influencing company value.